KEPADATAN EPIFAUNA DI LINGKUNGAN MANGROVE DESA LUBUK KERTANG KECAMATAN BRANDAN BARAT KABUPATEN LANGKAT PROVINSI SUMATERA UTARA - Buana Sukri Tanjung; Yunasfi Djayus; Tajuddin Siregar (AQUACOASTMARINE, 2018)
The mangrove ecosystem is a system in nature where life that reflects the mutual relationship between living creatures and their environment, affected by the tides of sea water and is dominated by species of trees or shrubs that are distinctive and able to grow in salty / brackish waters. This research was conducted by using Purposive Sampling method to know Epifauna Density in Environment Mangrove Lubuk Kertang Village. The results of this study indicate that the highest density of Cerithidea alata species (9500 ind / ha) because this species is native to mangrove forest and as a predator. Temperature ranges from 27-32 oC. Based on the Morisita Index the dispersion pattern by clumping.Keywords: Mangrove Ecosystem, Density, Epifauna